Opening the genetic toolbox of niche model organisms with high throughput techniques: Novel proteins in regeneration as a case study. (12th February 2014) - Looso, Mario
Abstract Understanding in vivo regeneration of complex structures offers a fascinating perspective for translation into medical applications. Unfortunately, mammals in general lack large‐scale regenerative capacity, whereas planarians, newts or Hydra can regenerate complete body parts. Such organisms are, however, poorly annotated because of the lack of sequence information. This leads to limited access for molecular biological investigations. In the last decade, high throughput technologies and new methods enabling the effective generation of transgenic animals have rapidly evolved. These developments have allowed the extensive use of niche model organisms as part of a trend towards the accessibility of a greater panel of model species for scientific research. The case study that follows provides an insight into the impact of high throughput techniques on the landscape of models of regeneration. The cases presented here give evidence of alternative stem cell maintenance pathways, the identification of new protein families and new stem cell markers.